Projekt naj športnica in naj športnik šole - Macura Kunej, Laura (Šport (Ljubljana), 2013)
Twenty years ago the Vižmarje Brod Primary School decided to start motivating the children for work through a project entitled "The best male and female athlete of the school". The aim of the project is to reward pupils for their school work and sport school and extra-curricular activities. The project involves all pupils from 6th to 9th class who compete, separated by gender. Each teacher keeps a record and is not dependent on other teachers in their choice of contents and competitions. The contents which are marked form part of the curriculum and are included in the teacherćs annual class schedule. The teacher submits it at the beginning of the school year and it is adapted to the school's spatial and material conditions. Throughout these years, thanks to the project and a positive attitude to work, consistency in implementation of the project, participation in school sport competitions as well as setting an example and showing respect to the subject we have succeeded in improving the attitude to work and fair play. In most cases, the motivation for work is positive, children no longer forget to bring their sports equipment and regularly monitor their own progress.
Keywords: competition; osnovne šole; physical education; primary school; sport; šport; športna vzgoja; tekmovanje